Synthesis of Brominated Quercetin Derivatives Using Distinct Brominating Systems - Peng, Mei; Liu, Fengxian; Feng, Xin; Yang, Fan; Yang, Xiaoping (Asian Journal of Chemistry, 2014)
6,8-Dibromoquercetin derivatives were obtained through reaction of quercetin with HBr-H2O2. On the other hand, quercetin reacted with bromine to synthesize poly brominated derivatives. The reaction procedures were monitored by either TLC or HPLC or both in some cases. The reaction products were further purified via either recrystallization or silica gel column chromatography. Then the chemical structures were further confirmed by 1H NMR and LC-MS. Two new quercetin brominated derivatives, namely 6,8-dibromoquercetin and 6,8,2',5',6'-pentabrominated quercetin were obtained. Two distinct brominated approaches were studied to obtain two different quercetin brominated derivatives, 6,8-dibromoquercetin and 6,8,2',5',6'-pentabrominated quercetin with the yields of 80 and 70 %, respectively.